Pelaksanaan Teknik Asesmen Formal dan Informal Pada Pembelajaran Matematika Untuk Anak Usia Dini: IMPLEMENTATION OF FORMAL AND INFORMAL ASSESSMENT TECHNIQUES IN MATHEMATICS LEARNING FOR EARLY CHILD - LATHIFAH HASANAH; KINANTI FITRIYANI; NARESWARI SABITHA WIDYADHARI; UZLIFA JANNAH; MIFTAHUL HASANAH (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
Assessment is a process of describing as it is about the behavior shown by the child. The behavior in question is directed at aspects of development that must be mastered by children. The assessment aims to reveal the facts of the actual development that occurs and is achieved by the child (description), mapping the developmental achievements of each child (mapping), grouping children on relatively similar developmental achievements (grouping), providing programs that are in accordance with the child's needs (programming). Implementation of the assessment can use two main approaches, namely a formal assessment approach (formal based assessment) and an informal assessment (informal based assessment). The formal assessment approach usually uses instrumentation and is based on scores or numbers, so some call it a test-based assessment. The informal assessment approach uses real situations and real work of children to describe the state of behavior as it is.